PENGARUH KERAGAMAN PRODUK, DISTRIBUSI, DAN WORD OF MOUTH TERHADAP KEPUTUSAN PEMBELIAN SEPEDA LISTRIK PADA TOKO SEPEDA GODA DI SITUBONDO DENGAN MINAT BELI SEBAGAI VARIABEL INTERVENING - Riskiyani, Vivi; Karnadi, Karnadi; Fandiyanto, Randika (Jurnal Mahasiswa Entrepreneurship (JME), 2024)
The aim of this research is to analyze the influence of product diversity, distribution and word of mouth on the decision to purchase an electric bicycle at the Goda bicycle shop in Situbondo with purchase intention as an intervening variable. The sampling technique was determined by simple random sampling. The data analysis and hypothesis testing in this research used the Partial Least Square Structural Equation Model (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 application show that product diversity has a significant positive effect on buying interest. The distribution has a positive but not significant effect on purchasing interest. The Information by Word of Mouth has a significant positive effect on buying interest. The product diversity has a positive but not significant effect on purchasing decisions. The distribution has a positive but not significant effect on purchasing decisions. The Information by Word of Mouth has a significant positive effect on purchasing decisions. The purchase interest has a significant positive effect on purchasing decisions. The product diversity has a significant positive effect on purchasing interest through purchasing decisions. The distribution has a positive but not significant effect on buying interest through purchasing decisions. The Information by Word of Mouth has a significant effect on buying interest through purchasing decisions.